MANAJEMEN RISIKO KEUANGAN DALAM TINJAUAN ISLAM - Setiawan, Iwan; Kusumadewi, Rahayu; Sari, Mega Permata; Astuti, Mentari Fuzi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
Every business has a certain amount of risk. It is difficult for us to accurately predict the future. No one in this world is able to predict the future exactly, even for a split second. Risk-taking is advantageous because there is always the possibility of something going wrong. Identification, analysis, assessment, control, and making every effort to prevent or eliminate hazards that are considered undesirable are all steps in the risk management process. Risk management is the process of organizing, controlling, and supervising the operation of an organization within a company. Reducing the likelihood that the company may suffer revenue losses is the goal of risk management. Risk management is the process of organizing, controlling, and supervising the operation of an organization within a company. Reducing the likelihood that the company may suffer revenue losses is the goal of risk management. Three elements are necessary for a risk management system namely: an appropriate environment for risk management, including good rules and processes; adequate techniques for measurement, mitigation, and monitoring; and appropriate internal control.